Realization of the tripartite alignment in Amahuaca: synchronic analysis and diachronic explanation - Valenzuela, Pilar (2023)
The native language Amahuaca (Panoan family, Peru) features a cross-linguistically unusual tripartite case-marking system whereby the subjects of intransitive and transitive verbs are signaled by means of the enclitics =x and =n, respectively, whereas the objects do not bear any morphological marking (Sparing-Chávez, 2007/2012; Clem, 2019a; among others). Another salient property of this system is the diverse realizations that nominals display when they host overt case-markers; this is, precisely, the primary focus of the present article. While these manifestations might initially appear erratic, our analysis reveals that the realizations of the marked nominals are highly predictable, especially when we posit the presence of a latent consonant that emerges phonetically in the context of =x and =n. From a diachronic perspective, we argue that this allomorphic variability can be linked to a rule proposed by Shell (1975), which is believed to have affected trisyllabic items in the protolanguage.